Adjuvant effects of Chinese medicinal tonics on gastric, liver, and colorectal cancers—OMICs-based contributions to understanding their mechanism of action - Zuo, Zhigang; Jia, Jia; Li, Hongliang; Shi, Run; Wang, Di; Zeng, Ke-Wu; Nie, Hong; Wang, Xin-Guo; Liu, Wen; Li, Minglun; Feng, Yibin; Wang, Xuan Bin (Frontiers in Pharmacology, 2022)
Gastric, liver, and colorectal cancers belong to gastrointestinal (GI) cancers, one of the most threatening diseases in the world. The tonics class in Chinese medicines plays a critical role in anti-gastrointestinal cancer as adjuvants. However, it is a challenge to study the effects and underlying mechanisms of tonics due to their multiple components and multiple targets; OMICs were introduced to facilitate the investigation of the complex mixture of tonics. In this review, the online databases, PubMed, ProQuest, Web of Knowledge, China National Knowledge Infrastructure (CNKI), Chongqing VIP and Wanfang were retrieved from January 1, 2011 to May 31, 2022, in an aim to summarize and discuss the research progress of the effects and especially the underlying mechanisms of tonics for anti-gastrointestinal cancers via OMICs. The results showed that through the combination of OMICs and other technologies, tonics have been used for gastrointestinal cancer by targeting cancer hallmarks, enhancing body resistance to carcinogenesis, enhancing therapeutic effects and/or decreasing side-effects. In conclusion, tonics may play a promising role in gastric, liver, and colorectal cancers as adjuvants and can be well investigated via the combination of OMICs and other technologies, which deserves further study.